Making Canadian Indian policy : the hidden agenda 1968-70 - Weaver, Sally M. (Studies in the structure of power, decision-making in Canada ;, 1981)
An analysis of the formulation of the Canadian government's White Paper on Indian policy based on interviews with individuals involved in shaping the policy, government documents and reports, and published materials.